The use of nominal group technique in promotion of healthy lifestyle - Moy, Foong Ming; Ab Sallam, Atiya (2004)
The nominal groups technique (NGT) was used as part of a needs assessment of a health promotion project on healthy lifesyle behaviour. Two aspects of healthy lifestyle behaviours which were physical exercise and healthy diet were selected by the participants. Two NGT groups were carried out simultaneously by two facilitators. A Likert scale of 1-10 was used to rank the importance of ideas generated during the discussion. The level of group support was ranked by the median while the level of agreement was rankedby the mean absolute deviation from the median. The representativeness of the NGT group was assessed with the subjects who did not participate in the NGT procedure. The level of agreement was observed to be higher in the NGT group for both the physical exercise and diet groups. The reason could be due to clarification and discussion which were carried out in the NGT group. The rank order of the exercise group did not differ in the NGTand the survey groups (Mann-Whitney U test, z=1.65, p=0.2), however the diet group showed different ranking with higher ranking from the survey groups (Mann-Whitney U test z=1.33, p=0.02). This could be due to the higher ranking assigned by the subjects in the survey group. Despite the difference in the ranking order in one of the groups, the researcher felt that the NGT outcomes are still representative of the larger group and will generate more infomation in developing a questionaire in the planning and implementation of the health promotion program.